Effect of elevated imipenem/cilastatin minimum inhibitory concentrations on patient outcomes in Gram-negative bloodstream infections. (June 2018) - McLaughlin, Milena M.; Miglis, Cristina; Skoglund, Erik; Wagner, Jamie; Advincula, Maria R.; Scheetz, Marc H.
Highlights: Patients receiving directed therapy were less likely to die, despite elevated carbapenem MICs. No relationship shown between receipt of carbapenem and mortality in patients with carbapenem-resistant Gram-negative BSI. Cefepime or piperacillin/tazobactam first directed therapy was associated with survival. Abstract: Objectives: Carbapenem minimum inhibitory concentration (MICs) are known to predict outcomes for patients with Gram-negative bacteraemia. However, limited data exist on how MICs influence such outcomes when organisms are classified as carbapenem-resistant. The purpose of this study was to evaluate the effect of increasing imipenem/cilastatin MICs on mortality in patients with Gram-negative bloodstream infection (BSI). Methods: Patients with an imipenem/cilastatin-resistant (MIC > 4 mg/L) monomicrobial Gram-negative BSI were eligible for inclusion in the study and were assessed for baseline characteristics, organ function, microbiological data, timing and type of therapeutic treatment, and in-hospital mortality. Results: A total of 62 patients with imipenem/cilastatin-resistant bacterial isolates (MIC > 4 mg/L) were retrospectively studied. Time to event analyses found no difference between patients who received carbapenem therapy and those who did not ( P  = 0.10). After adjustment, patients receiving directed therapy were less likely to die (adjusted hazard ratio = 0.35, 95% confidence interval 0.15–0.83; P <  0.01), whereas higher modified Acute Physiology and Chronic Health Evaluation (APACHE) II score and days to positive culture were associated with non-survival. Conclusion: This study did not demonstrate a relationship between receipt of a carbapenem and mortality in patients with carbapenem-resistant Gram-negative BSI.